Ibridazioni balzachiane «Meditazioni eclettiche» su romanzo, teatro, illustrazione - Fierro, Anna (Premio Ricerca «Città di Firenze», 2013)
The hybridisation of different arts and genres is one of the peculiar aspects of Balzac's aesthetics, whose writings surprise for their originality and unsuspected modern perspective. In the first and second part of the thesis, the intersection points between novel and theatre will be analysed, while in the third it will be shown how these two genres, in a deep relation with the illustration, give life to atypical texts that sometimes cannot be classified or that appear anti-canonical, revealing another side of Balzac's poetics. Each section is made up of texts, whose specificity lies in the ability to combine different styles, languages, arts, exposing the mechanisms proper to 'mélange': theatricality in narrative works; the novel in the theatre; the inclusion of the image in the text; and Balzac's mode of writing, which is modelled on the uniqueness of each phenomenon.